Realizing Recovery: the U.S. Substance Abuse and Mental Health Services Administration’s Efforts to Foster Social Inclusion - del Vecchio, Paolo; Nugent, Catherine; Townsend, Wilma; Torres, Ivette; Baker, Marsha (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2012)
For nearly 20 years, the U.S. Substance Abuse and Mental Health Services Administration (SAMHSA) has fostered social inclusion for Americans with mental and/or substance use disorders. SAMHSA has done this by promoting the recovery paradigm, an approach predicated on a positive, strength-based, and person-centered view of those with behavioral health conditions. SAMHSA has provided leadership by promoting policies, programs, practices, and public awareness initiatives that advance recovery, recovery support services, and recovery-oriented service delivery systems. SAMHSA’s approach has been participatory, engaging a variety of stakeholders, and comprehensive, focusing on multiple strategies in targeted priority areas.